2022
DOI: 10.3390/cancers14030522
|View full text |Cite
|
Sign up to set email alerts
|

NanoString Digital Molecular Profiling of Protein and microRNA in Rhabdomyosarcoma

Abstract: Purpose: Rhabdomyosarcoma (RMS) exhibits a complex prognostic algorithm based on histologic, biologic and clinical parameters. The embryonal (ERMS) and spindle cell-sclerosing RMS (SRMS) histologic subtypes warrant further studies due to their heterogenous genetic background and variable clinical behavior. NanoString digital profiling methods have been previously highlighted as robust novel methods to detect protein and microRNA expression in several cancers but not in RMS. Methods/Patients: To identify progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Utilization of the NanoString digital profiling technology in different prognostic groups of ERMS and spindle-cell sclerosing RMS (SRMS) patients revealed significant upregulation of either oncomiR or tumor suppressive miRNA ( 147 ). Of note, SRMS is biologically heterogeneous and like ERMS, it harbors a variety of genetic mutations that can result in different clinical outcomes.…”
Section: Oncomir Implicated In Rmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of the NanoString digital profiling technology in different prognostic groups of ERMS and spindle-cell sclerosing RMS (SRMS) patients revealed significant upregulation of either oncomiR or tumor suppressive miRNA ( 147 ). Of note, SRMS is biologically heterogeneous and like ERMS, it harbors a variety of genetic mutations that can result in different clinical outcomes.…”
Section: Oncomir Implicated In Rmsmentioning
confidence: 99%
“…This study revealed differential expression of miRNA between the different prognostic groups. For example, miR-612, miR-3144-3p, miR-548y, miR-302d-3p, miR-421, miR-548y and miR-548ar-5p were significantly overexpressed in tumors with adverse/poor prognosis compared to those with favorable prognosis ( 147 ). These may be interesting miRNA players in RMS development and progression, but their specific roles in RMS have not been determined.…”
Section: Oncomir Implicated In Rmsmentioning
confidence: 99%
“…Characterization of the tumor microenvironment while maintaining spatial orientation has become an essential resource for the understanding of complex immune cell interactions and the assessment of biomarkers for prognosis and prediction of immunotherapy response. The Nanostring GeoMx DSP platform [19,20,25] allows for characterization of the tumor microenvironment through high-plex digital quantification of proteins and mRNA from FFPE tissues with spatial resolution [26]. The application of spatial technologies to large numbers of patient samples that are available in pathology archives as FFPE blocks potentially provides unparalleled insight into cell types, cell location, biomarkers, and the interactions that may underlie disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…The DSP assay (NanoString Technologies, Seattle, WA, USA) was performed as previously described [28]. Following tissue rehydration and antigen retrieval, the slide was stained with the 4 morphology markers and 57 quantifiable antibodies (all NanoString Technologies, Seattle, WA, USA).…”
Section: Digital Spatial Profiling (Dsp Nanostring)mentioning
confidence: 99%